Become the real deal : - Dieken, Connie (New Jersey John Wiley & Sons, Inc., 2013)
Presents advice for improving personal influence by becoming, and being seen as being, the "real deal," or a person with the genuine leadership qualities of inner presence, verbal presence, and outer presence.